The Effect of Brand Image, Product Quality and Lifestyle on The Purchase Decision of Iphone Smartphones in Students of The Faculty of Social Sciences and Law, Makassar State University - Siti Annisa Nur Rahmah; Haedar Akib; Muh. Rizal S (Public Resource Innovation Management and Excellence, 2026)
Studi is examines the effect of brand image, product quality and lifestyle on purchasing decisions for iPhone brand smartphone products for students of the Faculty of Social Sciences and Law, Makassar State University partially and simultaneously. The purpose of this study was to determine the effect of brand image, product quality and lifestyle on purchasing decisions for iPhone brand smartphone products for students of the Faculty of Social Sciences and Law, State University of Makassar partially and simultaneously. This research approach is quantitative. This research was carried outinFaculty of Social Sciences and Law, Makassar State University. Respondents in the study werestudentFaculty of Social Sciences and Law, Makassar State University. Data collection techniques in the form of observation, questionnaires, and documentation. Data analysis techniques include statistical tests, validity tests, reliability tests, normality tests, descriptive analysis, multiple linear regression analysis, and analysis of the coefficient of determination.”Resultsiistudy“showing the effect of brand image on purchasing decisions, it was found that it did not have a contributing influence on purchasing decisions on students of the Faculty of Social Sciences and Law, Makassar State University. The effect of product quality on purchasing decisions, it was found that it had a significant influence on purchasing decisions for iPhone products for students of the Faculty of Social Sciences and Law, Makassar State University. The effect of lifestyle on purchasing decisions, it was found that it had a significant influence on purchasing decisions for iPhone products for students of the Faculty of Social Sciences and Law, Makassar State University. The influence of brand image, product quality, and lifestyle on purchasing decisions,”